Personal identification and sex determination using cheiloscopy - Ravindra Naik Gugulothu; Ravi Kiran Alaparthi; Kotya Naik Maloth; Sunitha Kesidi; Vinay Kundoor; Mallika Mahalakshmi Palutla (Wolters Kluwer Medknow Publications, 2015)
Introduction: Identification of an individual is a prerequisite for certification of death and for personal, social, and legal reasons. The study of lip prints (cheiloscopy) was thought of as a method of identification of a person. It is safe to assume that cheiloscopy, in its present stage of development, has become a means of criminal identification dealing with lip prints. Aims and Objectives: To evaluate the lip prints of different individuals in various parts of the lip, to find out the incidence of any particular pattern in relation to specific gender, to ascertain the authenticity of lip prints as a tool for identification of an individual and establish its evidentiary value. Materials and Methods: The study was conducted on 500 subjects, which included 250 males (4 twins) and 250 females, in the age group of 18-30 years. After application of lipstick evenly, the lip print of each subject was obtained on a simple bond paper. The lip prints of each individual were scanned using an image scanner set at a resolution of 600 dpi for better interpretation. Results: We had correctly matched the gender of 487 individuals out of 500 samples taken. We also found that no lip prints were similar among the 500 subjects and even in twins. Interpretation and Conclusion: Along with other traditional methods, cheiloscopy can also serve as a very important tool in the identification of a person based on the characteristic arrangement of lines and grooves appearing on the red portion of the lips. It can be used for sex determination and personal identification for forensic purposes.